Investigação do papel modulador do Haloperidol sobre os níveis de proteínas relacionadas à plasticidade e preferência por objetos novos em camudongos - Aguiar, Larissa Muratori (2013)
Dopamine (DA) is known to regulate both sleep and memory formations, while sleep plays a critical role in the consolidation of different types of memories. We believe that pharmacological manipulation of dopaminergic pathways might disrupt the sleep-wake cycle, leading to mnemonic deficits, which can be observed in both behavioral and molecular levels. Therefore, here we investigated how systemic injections of haloperidol (0.3 mg/kg), immediately after training in dark and light periods, affects learning assessed in the novel object preference test (NOPT) in mice. We also investigated the hippocampal levels of the plasticity-related proteins Zif-268, brain-derived neurotrophic factor (BDNF) and phosphorylated Ca2+/calmodulin-dependent protein kinases II (CaMKII-P) in non-exposed (naïve), vehicle-injected controls and haloperidol-treated mice at 3, 6 and 12 hours after training in the light period. Haloperidol administration during the light period led to a subsequent impairment in the NOPT. In contrast, preference was not observed during the dark period neither in mice injected with haloperidol, nor in vehicle-injected animals. A partial increase of CaMKII-P in the hippocampal field CA3 of vehicle-injected mice was detected at 3h. Haloperidol-treated mice showed a significant decrease in the dentate gyrus of CaMKII-P levels at 3, 6 and 12h; of Zif-268 levels at 6h, and of BDNF levels at 12h after training. Since the mnemonic effects of haloperidol were only observed in the light period when animals tend to sleep, we suggest that these effects are related to REM sleep disruption after haloperidol injection